Impact of Subsidies on the Economic and Environmental Conditions of Small Scale Fisheries in Malaysia - Islam, Gazi Mohammed Nurul; Ali, Jamal; Zamhuri, Saifoul; Viswanathan, K. Kuperan; Abdullah, Hussin (International Journal of Economics and Financial Issues, 2016)
This paper examines the economic and environmental impacts of fisheries subsidies on the small scale fisheries in Malaysia. The data for this study was obtained from interviews with 246 fishers from Kedah, Terengganu and Selangor states using a structured questionnaire. The study found that fishing effort and catch was significantly higher for commercial fishing boats operating in zone B and zone C compared to the artisanal fishing boats operating in zone A. The results suggest that fishing effort and catch was partly attributed to the fuel subsidy in fisheries. Furthermore, the larger engine boats (B and C) gained substantial fishing income that seems to reflect unequal distribution of benefits because larger vessels were able to gain maximum benefits compared to the smaller boats. However, the poor fishers (Boat A) were able to improve their livelihoods through various livelihood subsidies compared to the fishers with larger boats (B and C). The results suggest that current fisheries subsidies may not lead to sustainable fisheries and income of small scale fishers. Fisheries overexploitation cannot be reduced by elimination of subsidy, effective planning and designing of subsidy programmes may improve the wellbeing of fishers in Malaysia. Keywords: Fisheries subsidy; artisanal fisheries; income; fishing effort; livelihoods JEL Classifications: H2, Q22